Residencial Serra Verde Um estudo sobre um empreendimento autogestionário e seus processos - Gabriel Dias Melo Alves Almeida (2020)
The subject of the self-management, in Brazil, gains strength in the 80s when the social movements that fight for houses began to organize themselves better and to propose through several actions the creation of a national system of social interest projects. This project aims to incorporate in the public housing politics the concepts of self-management with the goal to promote broader independence and participation by the homeless population. In Belo Horizonte, the first experiences of this kind happened in 1996 and were realized through a city public politic called “Programa de Produção de Conjuntos Habitacionais por Autogestão”. This initiative, was financed by the city’s Community budget and, until the beginning of the 2000s, it has as result the construction of eleven housing projects, those projects totalized approximately 1.200 home unities, most of them constructed as lofts. In 2005, it was created by the federal government a new housing public politic that included a financial mode in the bank “Caixa Econômica Federal” destined to self- managed housing enterprises, it was called “Crédito solidário”. With this financialmode, the city’s politics ended in favor of the national program. The “Residential Serra Verde”, also known as the Red Sea Residential, was an attempt to seize this new moment of self-management in the country to advance in the discussion of the theme, this brought the capacity of self-management to the processes of the architectonical without the limit of the moment of the construction, as they were made during the experimental time in Belo Horizonte. This created a methodology of participative project that could be replicated in other enterprises. Therefore, what was intended in this paper is a critical reading of the strategies and difficulties presented during the work in the “Residencial Serra Verde”. And, with this, seek to present the goals that were reached, the results and the experiences owned in the field of the social interest, as the discussion about self-management as na alternative to the social housing production.